Ways Of Using Foreign Experience in Improving Corporate Management in Uzbekistan (Open Academia: Journal of Scholarly Research, 2024)
This article describes the modern system of corporate governance, its foreign experience, development trends in corporate governance practices and models in the world. In particular, the article discusses new views and reforms of corporate governance in the countries of the world in the 21st century, and also provides recommendations on the usage of best practices for improving corporate governance in Uzbekistan